Relativism and Post-Truth in Contemporary Society Possibilities and Challenges (Springer International Publishing, 2018)
This book approaches post-truth and relativism in a multidisciplinary fashion. Researchers from astrophysics, philosophy, psychology, media studies, religious studies, anthropology, social epistemology and sociology discuss and analyse the impact of relativism and post-truth both within the academy and in society at large. The motivation for this multidisciplinary approach is that relativism and post-truth are multifaceted phenomena with complex histories that have played out differently in different areas of society and different academic disciplines. There is hence a multitude of ways in which to use and understand the concepts and the phenomena to which they refer, and a multitude of critiques and defenses as well. No single volume can capture the ongoing discussions in different areas in all their complexity, but the different chapters of the book can function as exemplifications of the ramifications these phenomena have had.